The Importance of Product/Service Quality for Frontline Marketing Employee Outcomes: The Moderating Effect of Leader-Member Exchange (LMX). Issue 1 (2nd January 2016) - Lindsey Hall, Kristina K.; Baker, Thomas L.; Andrews, Martha C.; Hunt, Tammy G.; Rapp, Adam A.
Abstract : Drawing from a social identity perspective of the organizational identification theory, we propose a model in which product and service quality serve as antecedents to frontline employee identification with the organization, which, in turn, is proposed to be positively related to job satisfaction, commitment, and customer orientation. The model also proposes leader-member exchange (LMX), which refers to the different types of relationships that leaders (i.e., supervisors) develop with each of their subordinates (i.e., employees), as a boundary condition for the associated outcomes. The model was tested using data collected from 265 employees of a business-to-business service industry firm. The overall model was supported. All hypotheses were supported, except for the moderating effects of LMX on the relationship between organizational identification and job satisfaction.